Ambient Carbon Monoxide and the Risk of Hospitalization Due to Chronic Obstructive Pulmonary Disease. Issue 12 (5th December 2014) - Tian, Linwei; Ho, Kin-fai; Wang, Tong; Qiu, Hong; Pun, Vivian C.; Chan, Chi Sing; Louie, Peter K. K.; Yu, Ignatius T. S.
Abstract : Data from recent experimental and clinical studies have indicated that lower concentrations of inhaled carbon monoxide might have beneficial antiinflammatory effects. Inhaled carbon monoxide has the potential to be a therapeutic agent for chronic obstructive pulmonary diseases (COPD). However, population-based epidemiologic studies of environmentally relevant carbon monoxide exposure have generated mixed findings. We conducted a time-series study in Hong Kong to estimate the association of short-term exposure to ambient carbon monoxide with emergency hospitalizations for COPD. We collected daily emergency hospital admission data and air pollution data from January 2001 to December 2007. We used log-linear Poisson models to estimate the associations between daily hospital admissions for COPD and the average daily concentrations of carbon monoxide while controlling for the traffic-related copollutants nitrogen dioxide and particulate matter with an aerodynamic diameter less than 2.5 μm. Results showed that ambient carbon monoxide was negatively associated with the risk of hospitalizations for COPD. After adjustment for levels nitrogen dioxide or particulate matter with an aerodynamic diameter less than 2.5 μm, the negative associations of carbon monoxide with COPD hospitalizations became stronger. The risk estimates were similar for female and male subjects. In conclusion, short-term exposure to ambient carbon monoxide was associated with a decreased risk of hospitalization for COPD, which suggests that carbon monoxide exposure provides some acute protection of against exacerbation of COPD.